ROLE OF BONE MINERAL DENSITY ADDED TO FRACTURE RISK ASSESSMENT TOOL IN THERAPEUTIC DECISION-MAKING FOR OSTEOPOROSIS IN A MALAYSIAN POPULATION - Niyaz, Mariyam; Mariyappan, Shanmugam; Lee, Hew Fen; Sim, Yeap Swan; Velaiutham, Shanty; Thambiah, Subashini; Ganapathy, Shubash Shander; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES To examine the role of bone mineral density (BMD) added to Fracture Risk Assessment tool(FRAX) in therapeutic decision-making for osteoporosis in a Malaysian population. METHODOLOGY Data were collated from four centers in Malaysia. This study included individuals ages 40 to 90 years old who underwent routine BMD. Patients who had metabolic bone disease or were on anti-osteoporotic treatment were excluded. Ten- year probability of major osteoporotic fractures (MOF) and hip fractures (HF) was calculated using FRAX+BMD and FRAX-BMD. Treatment recommendations for FRAX+BMD and FRAX-BMD were compared and categorized as ‘concordant’ and ‘discordant.’ RESULTS A total of 1381 participants were included in the study, with the majority being female. There was strong correlation between FRAX+BMD and FRAX-BMD for both MOF (r = 0.889, p<0.001) and HF (r = 0.796, p<0.001). Concordance of 80.1% (p<0.001) was seen in treatment recommendation between FRAX+BMD and FRAX-BMD (treatment recommended n = 505; no treatment recommended, n=601). Concordance was highest in the youngest and eldest age groups with 91.1% and 85.8%, respectively. Among the discordant, FRAX-BMD underestimated treatment recommendation in 147 (10.6%) and overestimated in 128 (9.2%) participants. Age was the sole important predictor of discordance in treatment recommendations comparing both groups. FRAX-BMD had the least underestimation of treatment among the 80 to 90-year-old group (0.9%) and least overestimation in the 40 to 69-year-old group (1.2%). CONCLUSION FRAX-BMD had a good correlation with FRAX+BMD in a Malaysian population and is an acceptable alternative for treatment decision-making in situations where BMD services are not readily available.